2021
DOI: 10.21037/apm-20-2140
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of domestic and imported gefitinib in patients with advanced non-small cell lung cancer

Abstract: Background: Gefitinib is a first-generation epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI). It was approved by the U.S. Food and Drug Administration (FDA) for clinical use in 2003. However, gefitinib has only come to China in recent years. Previous studies have not compared the efficacy and safety of domestic and imported gefitinib. Therefore, we conducted this study. Methods: This study included 227 patients with advanced non-small cell lung cancer (NSCLC) who received

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…23) In 2003, the FDA approved gefitinib for the treatment of locally advanced or metastatic NSCLC patients who had received chemotherapy or had contraindications to chemotherapy. 9) Gefitinib was not considered to have significant cardiotoxicity. 11) However, in recent years, there have been many reports of gefitinib-induced cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23) In 2003, the FDA approved gefitinib for the treatment of locally advanced or metastatic NSCLC patients who had received chemotherapy or had contraindications to chemotherapy. 9) Gefitinib was not considered to have significant cardiotoxicity. 11) However, in recent years, there have been many reports of gefitinib-induced cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…7,8) Gefitinib is a first-generation epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI). 9,10) Different from other TKIs, gefitinib is not considered to have significant cardiotoxicity. 11,12) However, in recent years, more and more literatures have reported that gefitinib induces cardiotoxicity, mainly including acute coronary syndrome, 8) recurrent myocardial infarction, 11) myocarditis, 13) and QT interval prolongation.…”
mentioning
confidence: 99%
“…They bind to the EGFR kinase region in a competitive ATP-binding manner, reversibly inhibiting EGFR kinase activity and thus blocking downstream signaling. (1) Gefitinib was approved by the FDA in 2003 for the treatment of patients with advanced NSCLC who have failed chemotherapy [107]. (2) Erlotinib was approved by the FDA in 2004 for the treatment of locally advanced or metastatic NSCLC and was subsequently approved in combination with gemcitabine for the treatment of locally advanced or metastatic pancreatic cancer [108].…”
Section: Egfr Inhibitorsmentioning
confidence: 99%
“…They bind to the EGFR kinase region in a competitive ATP-binding manner, reversibly inhibiting EGFR kinase activity and thus blocking downstream signaling. 1) Gefitinib Gefitinib was approved by the FDA in 2003 for the treatment of patients with advanced NSCLC who have failed chemotherapy [105]. Erlotinib was approved by the FDA in 2004 for the treatment of locally advanced or metastatic NSCLC and was subsequently approved in combination with gemcitabine for the treatment of locally advanced or metastatic pancreatic cancer [106].…”
Section: Egfr Inhibitorsmentioning
confidence: 99%